Development of specific coordination abilities and vestibular stability in the course of physical training of cadets of NANGU - Савчук, Павло; Шестерова, Людмила (Slobozhanskyi Herald of Science and Sport, 2016)
Savchuk, P. & Shesterova, L. Purpose: to develop and to check experimentally ways of increase in specific coordination abilities of cadets of NANGU. Material & Methods: analysis and synthesis of references, pedagogical observations, testing, test of Yarotskyi; pedagogical experiment; modeling. Cadets of 2 and 3 courses of NANGU participated in the research. Results: the specific coordination abilities, which are shown at cadets of NANGU in the course of the solution of motive problems of military-applied orientation, are defined; the technique of definition of vestibular stability and assessment of its results on data of the test of Yarotskyi is mastered; the efficiency of experimental training of method of vestibular stability of cadets of NANGU is developed and defined. Conclusions: the expediency of introduction in the educational process on physical training of cadets of NANGU of experimental training of method of vestibular stability is proved.